The determination of antioxidants activity and sunblock Sterculia populifolia extract- based cream - Nur Khairi; Suryani As'ad; Khaeruddin Djawat; Gemini Alam (Mazandaran University of Medical Sciences, 2018)
Sterculia populifolia is commonly used as the ingredient of traditional herb in Timor Island, East Nusa Tenggara, Indonesia. It contains flavonoid which roles as antioxidant. This flavonoid can be sunblock due to the existence of chromophore which commonly gives color to plants. This study aimed to determine the activity of antioxidants and sunblock through the value of Sun Protection Factor (SPF) from Sterculia populifolia extract-based cream and cream preparation extract. This cream was formulated into four formulas; extract concentrate 0% (F0), 1% (F1), 3% (F2) and 5% (F3). The result showed that the whole formula of cream preparation filled the physical stability parameter. F3 cream had IC50 79.179 ppm value while SPF had 5.6 value higher than F1 and F2. The smaller the IC50 value, the bigger antioxidant activity and SPF increased.